1992
DOI: 10.1046/j.1469-0705.1992.02050338.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of pulsatility and resistance indices in classification of adnexal tumors with transvaginal color Doppler ultrasound

Abstract: Transvaginal pulsed color Doppler ultrasound was used to examine 72 patients with a pelvic mass preoperatively. Tumor morphology was assessed, prominent areas of vascularization within the tumor were observed and the pulsatility index and the resistance index of tumor and uterine arteries were measured. Flow velocity waveforms with low pulsatility are considered to reflect neovascularization. The ultrasound diagnoses were compared with histopathological or cytological diagnoses. There were 61 benign, eight mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
4
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 0 publications
5
46
4
6
Order By: Relevance
“…The results have been controversial. Some authors have found this technique useful 2 -10 , whereas others have not [11][12][13][14][15][16][17] . Some factors put forward to explain these conflicting results include differences in sonographers' experience, different sensitivity in ultrasound machines and the lack of standarization of Doppler measurements 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results have been controversial. Some authors have found this technique useful 2 -10 , whereas others have not [11][12][13][14][15][16][17] . Some factors put forward to explain these conflicting results include differences in sonographers' experience, different sensitivity in ultrasound machines and the lack of standarization of Doppler measurements 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors have found this technique useful [2][3][4][5][6][7][8][9][10] , others have questioned these results [11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, individual sonographic, demographic, and biochemical variables were used to distinguish between benign and malignant adnexal masses 4 . However, used alone, the diagnostic accuracy of these variables was poor.…”
Section: Two-and Three-dimensional Doppler Ultrasound Analysis Of Abdmentioning
confidence: 99%
“…Despite now decades of observations and improved imaging technology, 2D images results in many surgeries for benign masses predicted to be cancer (PPV varying from 40-96 %). [3][4][5][6] The original description of "tumor vascularity" is credited to Strickland (1959). In his study of bone tumors, Strickland described a tumor vessel as one that was "deployed seemingly without purpose, and keeps to no set course and shows no progressive diminution in caliber."…”
Section: Introductionmentioning
confidence: 99%